Transliteration of Indonesian Geographical Names into Chinese - Qin Weifen; Wang Difei (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
In this paper, a comparative analysis of the phonetics between Indonesian and Chinese in the geographical name conversion process is carried out to investigate the way of Chinese transliterating for Indonesian geographical names, in order to standardize Chinese proper translation for Indonesian geographical names. The author found that in general, people will translate geographical names by transliterating for specific parts of the name, and paraphrasing for generic names. Processing of vowels and consonants has different characteristics in the transliteration process, which generally according to Chinese pronunciation habits. And some geographical names are translated directly into Chinese dialects. This contains a wealth of immigrant cultural information and dialect information, which can infer the general distribution of early Chinese immigrants in Indonesian settlements, guide significance for the study of Chinese society and culture. In addition, Chinese transliterated names for Indonesian geographical names in different historical periods are subject to change.